Growth factor independence 1 ameliorates osteoarthritis by inhibiting chondrocyte ferroptosis via inactivation of MAPK signaling pathway - Xiaoyu Jin; Xunhao Wang; Siyu Xu; Nuo Xu; Ziwei Wang; Chunqing Hu; Wei Liu; Zhaofeng Zhang; Xiyu Liu; Jingjing Fan; Ruiyang Jiang; Rui Wu; et al. (Journal of Orthopaedic Translation)
Background: Osteoarthritis (OA) is the most common degenerative joint disease, characterized by cartilage deterioration, which is closely associated with chondrocyte ferroptosis. The aim of this study was to investigate the role and mechanism of previously unexplored gene, growth factor independence 1 (Gfi1) in chondrocyte ferroptosis, in order to provide a new therapeutic target for OA. Methods: The expression of ferroptotic hallmarks and Gfi1 were analyzed in human and mice OA cartilages and tert-butyl hydroperoxide (TBHP)-induced primary chondrocytes. Small interfering RNA or overexpression plasmids were used to knock down or overexpress Gfi1 to explore its role in chondrocyte ferroptosis and metabolism. Then, the role of Gfi1 in destabilization of medial meniscus (DMM) surgery-induced mice OA model was investigated with or without the intra-articular injection of adeno-associated virus-overexpressing Gfi1 (AAV-Gfi1). Furthermore, RNA sequencing analysis was performed to reveal the key downstream pathway of Gfi1 exerting its role in chondrocyte ferroptosis. Results: The expression of Gfi1 was significantly decreased, while 4-HNE, a typical lipid peroxidation product, was significantly increased both in damaged human and DMM surgery-induced mice OA cartilages. Consistently, Gfi1 was remarkably downregulated in TBHP-induced ferroptotic chondrocytes. Moreover, Gfi1 knockdown aggravated chondrocyte ferroptosis by elevated levels of ferroptotic hallmarks, including total ROS, lipid ROS and Fe2+ accumulation. The upregulation of ferroptotic driver (Cox2, Acsl4) and catabolic marker (Mmp13) and downregulation of ferroptotic suppressors (Gpx4, Fth1, Slc7a11) and anabolic marker (Col II) were also observed in TBHP-induced chondrocytes by Gfi1 knockdown. On the contrary, Gfi1 overexpression showed anti-ferroptotic effect in TBHP-induced chondrocytes. Intra-articular injection of AAV-Gfi1 evidently alleviated cartilage degeneration by resisting ferroptosis and preserving the anabolism-catabolism homeostasis in OA cartilages. Comprehensive evaluation of subchondral bone sclerosis, osteophyte formation, synovitis and behavior performance further validated that Gfi1 overexpression ameliorated OA progression. Mechanistically, MAPK signaling pathway was identified as the key downstream mediator of Gfi1 exerting anti-ferroptotic role in OA. Conclusion: Gfi1 is downregulated in OA and its overexpression ameliorates OA progression by inhibiting chondrocyte ferroptosis via inactivation of MAPK signaling pathway. The translational potential of this article: This study identifies Gfi1 as a novel therapeutic anti-ferroptotic target for cartilage degeneration, providing more clues for optimizing OA treatment strategies in clinical practice.